A systematic review and meta-analysis of prevalence of seven psychiatric disorders in India - Vikas Dhiman; Geetha R. Menon; Rajnarayan R. Tiwari (Indian Journal of Psychiatry)
Background: After the National Mental Health Survey in 2016, multiple individual studies showed inconsistencies in the prevalence rates of psychiatric disorders in India. We performed a meta-analysis to estimate an up-to-date pooled estimate of the prevalence of depression, alcohol use disorder (AUD), anxiety disorder (AD), intellectual disability, suicidal attempt/death, autism, and bipolar disorder (BD) in India. Materials and Methods: We performed a systematic bibliographic search in Pub Med, Global Health Data Exchange (GHDx), and Google Scholar, along with a manual search for peer-reviewed epidemiological studies reporting the prevalence of depression, AUD, AD, MR, suicidal attempt/death, autism, and BD in India from January 1980 till March 2022. Adopting a random-effects model, we performed the meta-analysis using “MetaXL” software. Results: A total of 79 studies were included: depression (n = 28), AUD (n = 14), AD (n = 12), intellectual disability (n = 8), suicidal attempt/death (n = 7), autism (n = 6) and BD (n = 4). The pooled prevalence of depression and AUD was 12.4% (95% CI 9.4–15.9) (P < 0.001, I2 = 100%) and 21.5% (95% CI 14.1–30.0) (P < 0.001, I2 = 100%), respectively. AD, intellectual disability and suicidal attempt/death showed a prevalence of 11.6% (95% CI 8.1–15.7) (P < 0.001, I2 = 99%), 1% (95% CI 0.5–1.6) (P < 0.001, I2 = 98%) and 0.5% (95% CI 0.3–0.8) (P < 0.001, I2 = 100%), respectively. The meta-analysis in autism and BD showed pooled prevalence of 0.3% (95% CI 0.1–0.6) (P < 0.001, I2 = 96%) and 0.3% (95% CI 0.2–0.4) (P < 0.001, I2 = 78%), respectively. Subgroup analysis showed an increased prevalence of AD in the urban [24.3% (95% CI 3.7–52.9)] and younger [16.7% (95% CI 5.1–32.7)] population. The prevalence of depression and AD increased during the last two decades on decadal prevalence analysis. Discussion: The findings could be used for appropriate policy measures and guiding subsequent national mental health surveys.